The Influence of Leadership and Work Discipline on Employee Performance at PT. Visionet Data Internasional Tangerang City - Suwanto Suwanto (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of leadership and work discipline on employee performance at PT. Tangerang City International Data Visionet. This research method is descriptive quantitative with a population of 80 employees and drawn as a saturated sample. The analytical method used in this research includes instrument data test, classical assumption test, linear regression test, correlation coefficient along with determination and hypothesis testing. Based on the results of the study that leadership has a positive and significant effect on employee performance, it is proven by a simple linear regression test Y = 20.701 + 0.396 X₁, with a hypothesis test t arithmetic > t table (3,818 > 1,664) strengthened by a sig value <0.05 then H1 is accepted . The work discipline variable has a positive and significant effect on employee performance with a simple linear regression test Y = 11,222 + 0.660 X₂, with a hypothesis test t arithmetic > t table (8,464 > 1.664) strengthened by sig value <0.05 then H2 is accepted. Leadership and Work Discipline simultaneously have a positive and significant effect on employee performance as evidenced by multiple linear regression Y = 2.461 + 0.117 X₁ + 0.826, the correlation coefficient r is 0.692 which indicates a strong level of relationship. The value of the coefficient of determination R² of 0.489 indicates that the influence of leadership and work discipline on employee performance is 48.9%. The results of the third hypothesis test are obtained by the calculated F value > F table, namely (36.833 > 3.12) then H3 is accepted.